Assessment of Knowledge on Key Features of Angle’s Class II Division 1 Malocclusion among Dental School Under-graduates - Kapoor, Deepika (Orthodontic Journal of Nepal, 2018)
Introduction: Angle in 1899 propounded the classification to recognize the malocclusion patterns. Class II Division 1 is a malalignment which can be identified by the parameters mentioned. Objective: To assess the knowledge of dental undergraduate students about Class II Division 1 malocclusion and their opinion about the treatment or clinical approach to such patients. Materials & Method: The study was performed using closed questionnaire on 138 fourth and final year undergraduate dental students of College of Dental Sciences, Bharatpur, Nepal. Dental casts and photographs of a patient with Class II Division 1 were shown to the respondents to depict deviated midline, midline diastema, molar relation, increased overjet and overbite. Result: Dental students found it easy to identify increased overjet (91.99%), increased overbite (88.78%), presence of diastema (84.69%) and midline deviation (77.28%). However, 52% students could not identify the molar relationship. When asked about the appropriate timing for treatment; 48.8% thought it should be in deciduous dentition period, 41.6% in mixed dentition, and 9.6% in permanent dentition. Conclusion: Fourth and final year BDS students possess fair knowledge on common parameters used to determine Class II Division 1 malocclusion but they find difficulties in compiling and applying this knowledge to orthodontic treatment concept.